Vegetation successions over 30 years of high country grassland invasion by Pinus contorta - Ledgard, N.J.; Paul, T.S.H. (New Zealand Plant Protection, 2008)
The invasion of a high country grassland site (850 m asl) by lodgepole or contorta pine (Pinus contorta Dougl) wildings was monitored over 32 years in the Craigieburn Range Canterbury The first wildings appeared in 1975 By 1985 density had reached 34550 stems/ha with a mean height of 185 m and a basal area of 17 m2/ha By 2007 stocking had dropped to 11400 stems/ha with a mean top height of 143 m and a basal area of 104 m2/ha Thirtyeight plant species were present 10 years after wilding invasion started Twentysix species (68) were indigenous By 2007 the number of species present had dropped to seven none of which were indigenous The introduced tussock hawkweed (Hieracium lepidulum) featured in both assessments It was concluded that more species are likely to invade as the canopy opens up but if native species are wanted they may have to be introduced by artificial seeding